Sportmanagement Reflexionen: Kommerzialisierung im Profifußball - mit oder ohne Fans - Dirk Gutzeit (IU Internationale Hochschule, 2021)
– Professional football generates billions in revenue in Germany alone. After fifteen consecutive revenue records, the Covid 19 pandemic is leading to revenue declines in the Bundesliga. Football fans have played a major role in these declines. They no longer go to the football stadiums week after week to loudly support their teams. Not because they don't want to, but because it is no longer allowed due to the pandemic since the sixth matchday of the current 2020/21 season. In addition to the findings of declining revenues due to the lack of ticket sales, there is also the question of the significance of fans in the context of advancing commercialisation. Could the current pandemic-related spectator exclusion possibly also enact thought processes to deliberately reduce fan participation?
Keywords: Z2; Z20; Z29; 650; Sportmanagement; Fußball; Profifußball; Fans; Zuschauer; Kommerzialisierung; Pandemie; Bundesliga